IMPLEMENTASI PENDIDIKAN INKLUSI PADA JENJANG PENDIDIKAN DASAR - Rohimah, Iim; Rafiadilla, Jihan; Patras, Yuyun Elizabeth (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
Inclusive education at the basic education level is very important in order to optimize the development of children with special needs according to their potential. However, the implementation of inclusive education at the basic education level still experiences many problems. The aim of this research is to describe the results of research related to the implementation of inclusive education at the basic education level. The method applied in this research is a literature review of articles in Indonesian and English in 2019-2023 sourced from the Google Scholar search site, scopus.com and ERIC. Through an inductive analysis approach, a match of data was found related to the implementation of inclusive education in elementary schools so that 15 relevant articles were selected. The data analysis procedure was carried out based on a qualitative approach. Research findings show that inclusive education can be implemented at the basic education level by involving all elements of education and the school community to be able to provide education and services to children with special needs so that they can develop based on their potential and socialize normally with their peers in regular schools. The new path or recommendation which can be implemented is that implementing inclusive education at the basic education level requires dedication from all elements of education and the school community to create comfortable and friendly education for children with special needs.